THE EFFECT OF USING INFORMATION SEARCH STRATEGY ON STUDENTS’ READING COMPREHENSION OF ANALYTICAL EXPOSITION TEXT AT ELEVENTH GRADE OF SMA NEGERI 1 SORKAM IN 2020/2021 ACADEMIC YEAR) - Asriani Hasibuan; Anna Maria Tarihohan (Journal MELT (Medium for English Language Teaching), 2021)
The goal of this study is to see if the Information Search strategy has a significant impact on students' reading comprehension of analytical exposition texts in eleventh grade students at SMA Negeri 1 Sorkam in the 2020/2021 Academic Year. This study employs an experimental approach with a pre-experimental research design, as well as a pretest-posttest design for one group. There are 187 students in the eleventh grade, therefore the population is made up entirely of them. Purposivesampling is the sampling technique utilized in this study, and the sample size is 31 students. The researcher collects data using an observation sheet for data on the implementation of the Information Search technique and a test for data on the students' reading comprehension of an analytical exposition text. The use of the Information Search approach yielded a score of 3.5, which is considered "very good." Before adopting the Information Search approach, the mean score of the students'reading comprehension of analytical exposition material. Before using the Information Search strategy, the students' reading comprehension of analytical exposition text had a mean score of 55, which was categorized as "Bad." Meanwhile, it was categorized as "Good" after using the Information Search strategy with a score of 70. The researcher uses the ttest formula to analyze the data using the statistical process. Based on the data that was analyzed, the data analysis revealed that ttest is superior to ttable (ttest9.02> ttable 2.04). As a result, the hypothesis has been accepted. It means that in the 2020/2021 Academic Year, there is a considerable influence of Information Search method on students' reading comprehension of analytical exposition text at SMA Negeri 1 Sorkam eleventh grade students.